Neoadjuvant Chemohormonal Therapy in Prostate Cancer Before Radical Prostatectomy: A Systematic Review and Meta-Analysis - Ge, Qingyu; Xu, Hewei; Yue, Dezhou; Fan, Zongyao; Chen, Zhengsen; Xu, Jie; Zhou, Yiduo; Zhang, Sicong; Xue, Jun; Shen, Baixin; Wei, Zhongqing (Frontiers in Oncology, 2022)
Objective This meta-analysis was to investigate the effects of neoadjuvant chemohormonal therapy (NCHT) on patients with prostate cancer (PCa) before radical prostatectomy (RP) and attempt to provide meaningful evidence. Methods A systematic search was performed using the PubMed, Web of Science, and Cochrane Library databases in February 2022 based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The relevant studies were critically screened and we extracted the data of demography, postoperative pathology, and survival to calculate the pooled effect sizes. Subgroup analyses and sensitivity analyses were used to explore the source of heterogeneity. Results Six identified studies involving 1717 subjects were included according to the selection criteria. There was no significant difference between NCHT plus RP and RP alone groups regarding lymph node involvement (risk ratio [RR]=1.03, 95% confidence interval [CI]: 0.57-1.87, P=0.92). However, NCHT prior to RP significantly decreased the rates of positive surgical margin (PSM, RR=0.35, 95% CI: 0.22-0.55, P<0.0001) and seminal vesicle invasion (SVI, RR=0.78, 95% CI: 0.65-0.95, P=0.01), and increase pathological downstaging (RR=1.64, 95% CI: 1.17-2.29, P=0.004). Additionally, biochemical recurrence-free survival (BRFS) and overall survival (OS) were significantly prolonged under the administration of NCHT (HR=0.54, 95% CI: 0.34-0.85, P=0.008 and HR=0.67, 95% CI: 0.48-0.94, P=0.02, respectively). Conclusions Compared to the RP alone group, patients with NCHT plus RP showed significant improvements in PSM, SVI, pathological downstaging, BRFS, and OS, whereas further multicenter randomized controlled trials are needed to consolidate this concept.